Teaching writing to Grade 5 English language learners in two Grahamstown East schools, South Africa : a case study - Julius, Lukas Homateni (Rhodes University, Faculty of Education, Department of Education, 2014)
The majority of learners in South Africa are not native speakers of English, yet English is the dominant language of learning and teaching (LoLT). South African teachers, therefore, have the challenge of ensuring that their learners' literacy skills in English are adequately developed so as to facilitate learning in other curricular areas. This study investigated the way in which two Grade 5 teachers employed at different primary schools in the Eastern Cape province of South Africa taught writing to their English first additional language (EFAL) learners. English is the LoLT at both schools. A qualitative interpretive approach was used to identify factors that shape the ways these teachers handle the teaching of writing. The theoretical framework was informed by Borg's model of teacher cognition (2003) Shulman's conception of teacher knowledge (1987). Data collection methods consisted of interviews, classroom observations and document analysis. In-depth interviews, comprising two semi-structured interviews, two post-lesson informal conversational interviews and one stimulated recall interview were conducted with each teacher. Five of each teacher's writing lessons were observed and audio and video recorded. Samples of learners' written work were also collected. Analysis of the data reveals that the two teachers' beliefs, their experiences as learners themselves and subsequently as teachers, impacted on their pedagogy, as did other contextual factors (including the support they received from subject advisors, time management, and the number and range of learners in their classrooms). It was found that both teachers focused primarily on ensuring that their learners completed their written work so that it could be marked and graded in response to demands from their superiors, rather than on engaging deeply with the processes of writing (brainstorming, drafting, revising etc). Not only does this run counter to the writing pedagogy recommended in the Curriculum and Assessment Policy Statements (CAPS), but it also denies learners the scaffolding needed to help them develop the self-regulation skills needed to become independent writers. These findings demonstrate the need for assisting teachers to shift away from focusing only on learners' performance (testing and grading) towards a stronger emphasis on the process of writing. This would require that teachers develop a deeper understanding of the process/genre approaches to teaching writing advocated by CAPS.
Keywords: English language -- Study and teaching (Primary) -- South Africa -- Grahamstown; English language -- Written English; English language -- Composition and exercises -- Study and teaching (Primary); English language -- Ability testing; Teacher effectiveness -- South Africa -- Grahamstown; Teachers -- Rating of -- South Africa -- Grahamstown; Written communication; Second language acquisition